KAJIAN TATA BANGUNAN DAN LINGKUNGAN KAWASAN PAOTERE DI KOTA MAKASSAR - Bunny Lisal (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Indonesia is an archipelagic country with a long coastline. Due to its archipelagic nature, many major cities have developed along the coast, and most of the coastal population consists of fishermen. Paotere in Makassar City began as a fishermen's settlement and a trading hub. The population in Paotere, particularly in Cambaya Village, has grown significantly, reaching 6,368 people in an area of 5.3 hectares (Makassar in Figures 2023). This equates to a population density of 1,201 people per hectare. This study focuses on a smaller area of 2.36 hectares. Uncontrolled population growth has led to the emergence of slum settlements in this region.As a result of inadequate urban planning, issues have arisen regarding the provision of infrastructure and facilities for residents, as well as a decline in environmental quality. This study employs a mixed-method approach, combining quantitative and qualitative descriptive methods, as part of a case study in the Paotere area, Cambaya Village, Ujung Tanah District, Makassar City. Data sources for this research include observation, documentation, and literature studies. The findings reveal environmental issues, such as limited access to clean water. Only 667 houses, out of a total of 1,050 in the Paotere area, are connected to the PDAM water supply network, meaning approximately 36% of homes lack access to clean water. Additionally, the residential area lacks a temporary waste disposal site. This research is expected to serve as a foundation for government or private institutions to improve and reorganize buildings and the environment in the Paotere area of Makassar City.